Ageratum conyzoides: Potential Therapeutic Agent for the Treatment of Bacterial Infections - Iqbal, Muhammad Naeem; Iqbal, Iqra (PSM Biological Research, 2024)
There is increasing interest in plant extracts as potential therapeutic agents. Plants remain an important source of raw materials for synthetic medications, despite significant advancements in the pharmaceutical sector. Research has shown that the identification of active compounds in medicinal plants has added to their value. Numerous therapeutic substances have been discovered via antimicrobial screening of traditional medicinal plants. In this issue, Aernan et al. determine the antibacterial activity of Ageratum conyzoides leaf extracts against test bacteria that may be due to polyphenolic compounds. The use of A. conyzoides plant parts as an antibacterial agent particularly requires further investigation.